MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM SENI MUSIK MELALUI PENDEKATAN KONTEKSTUAL PADA MATERI RAGAM LAGU DAERAH NUSANTARA - Nugraha, Anggi Anggriyana; Julia, Julia; Subarjah, Herman (Jurnal Pena Ilmiah, 2017)
The purpose research is critical thinking ability increasing in the music art of Tegalkalong Elementary School’s the fifth-B class Of North Sumedang Subdistrict, Sumedang Regency of the archipelago song of variety material with contextual approach using. The research is one of the class action research with 24 students. The research is doing by the third cycles of using Kemmis and Mc. Taggart’s self-reflection spiral model which divided from planning, implementation, observation, and reflection. The using instruments are observation, evaluation, interview, and field note. Lots of target have reached in the third cycle. Attainment percentage is 100% for teacher performance in the planning, 100% for teacher performance in the implementation, 89,81% for student activity, and 87,5% the critical thinking ability of resultant. The research resultant is inferential that using of contextual approach is able to increase teacher performance in the planning, implementation, student activity, and studying resultant of the critical thinking increasable.